Development of performance assessment models for glass dissolution. Issue 63 (20th February 2017) - Goto, T.; Mitsui, S.; Takase, H.; Kurosawa, S.; Inagaki, M.; Shibata, M.; Ishiguro, K.
ABSTRACT: NUMO and JAEA have been conducting a joint research since FY2011, which is aimed to enhance the methodology of repository design and performance assessment in preliminary investigation stage for the deep geological disposal of high-level radioactive waste. As a part of this joint research, we have been developing glass dissolution models which include various processes derived from glass-overpack-bentonite buffer interaction, considering the precipitation of Fe-silicates associated with steel overpack corrosion, and Si transport through altered layer of glass. The objective of this modeling work is to show comprehensively the lifetime of the vitrified waste due to glass matrix dissolution timescales through sensitivity analysis, and to identify the feature/process that most strongly influences the lifetime, and to identify future R&D issues that would help to improve the nuclide transport analysis with confidential value and the safety case in future. The sensitivity analysis suggested that the duration of the glass dissolution might be predicted in the ranges from 3.8×10 3 to 1.9×10 5 years. Also, the results indicated that the precipitation of Fe–silicate has the strongest influence on the long-team behavior of vitrified waste.